Infrared optical responses of wurtzite InxGa1 − xN thin films with porous surface morphology - Yew, P.; Lee, S.C.; Ng, S.S.; Abu Hassan, H.; Chen, W.L.; Osipowicz, T.; Ren, M.Q. (Elsevier B.V., 2016)
Room temperature infrared (IR) optical responses of wurtzite indium gallium nitride (InxGa1 − xN) in the composition range of 0.174 ≤ x ≤ 0.883 were investigated by the polarized IR reflectance spectroscopy. Analyses of the amplitudes of oscillation fringes in the non-reststrahlen region revealed that the high frequency dielectric constants of the samples were unusually smaller than the values predicted from the Clausius–Mossotti relation. This odd behavior was attributed to the porous surface morphology of the InxGa1 − xN samples. The E1 optical phonon modes of the InxGa1 − xN were deduced from the composition dependent reststrahlen features. The obtained values were compared to those calculated through the modified random element iso-displacement (MREI) model. The deviation between the measured data and the MREI model prediction were explained in detail from the aspects of strain, thermal expansion and anharmonic phonon-coupling. Finally, it was found that the large discrepancy of the E1(LO) mode is mainly attributed to the effects of the longitudinal phonon–plasmon coupling.